14th Annual Meeting of the Safety Pharmacology Society: threading through scientific sessions for originality and novelty. (June 2015) - Cavero, Icilio
<x xml:space="preserve">Abstract</x> Introduction: The Annual Meeting of the Safety Pharmacology (SP) Society is a yearly event designed to keep attendees abreast of how to best identify and mitigate organ function liabilities of candidate drugs selected for clinical assessment. Areas covered: Heart rate (HR) and blood pressure (BP) effects of candidate drugs in dogs/monkeys have satisfactory human translation. Mechanism-designed assays offer opportunities for innovative approaches to identify chemotherapeutic-induced peripheral neuropathy (PN). SP has a large array of methodologies to determine safety on eye functions. Video-tracking analysis of zebrafish swimming behavior accurately profiles drugs for high-level brain function liabilities. Available in vitro and in vivo assays can identify, and determine physiological and pharmacological mechanisms of, candidate drug-induced emesis. Ad hoc Working Groups have already finalized protocols for testing the comprehensive in vitro arrhythmia assay (CiPA), an innovative paradigm for assessing mechanisms conferring candidate drug proarrhythmic liabilities. Expert opinion: The good concordance of non-clinical and clinical Phase I BP and HR effects of candidate drugs support the use of dog/monkey models for clinical outcome. Drug liabilities (e.g., PN, nausea, vomiting, etc.) affecting non-vital organs/systems require the same degree of SP attention given to vital functions as they can dramatically reduce patient quality of life.